15+19y+19=-19y-3(-15y+19)

Simple and best practice solution for 15+19y+19=-19y-3(-15y+19) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15+19y+19=-19y-3(-15y+19) equation:


Simplifying
15 + 19y + 19 = -19y + -3(-15y + 19)

Reorder the terms:
15 + 19 + 19y = -19y + -3(-15y + 19)

Combine like terms: 15 + 19 = 34
34 + 19y = -19y + -3(-15y + 19)

Reorder the terms:
34 + 19y = -19y + -3(19 + -15y)
34 + 19y = -19y + (19 * -3 + -15y * -3)
34 + 19y = -19y + (-57 + 45y)

Reorder the terms:
34 + 19y = -57 + -19y + 45y

Combine like terms: -19y + 45y = 26y
34 + 19y = -57 + 26y

Solving
34 + 19y = -57 + 26y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-26y' to each side of the equation.
34 + 19y + -26y = -57 + 26y + -26y

Combine like terms: 19y + -26y = -7y
34 + -7y = -57 + 26y + -26y

Combine like terms: 26y + -26y = 0
34 + -7y = -57 + 0
34 + -7y = -57

Add '-34' to each side of the equation.
34 + -34 + -7y = -57 + -34

Combine like terms: 34 + -34 = 0
0 + -7y = -57 + -34
-7y = -57 + -34

Combine like terms: -57 + -34 = -91
-7y = -91

Divide each side by '-7'.
y = 13

Simplifying
y = 13

See similar equations:

| f(x)=2x-3/4=0 | | t^4-t^2-1=0 | | 5j=5(6j-10) | | 3(2)+y=12 | | 3x/5-6=9 | | 3(6)+y=12 | | x+11=2x-1 | | -7+6(-4q+19)=20-3-19q | | 3(4)+y=12 | | 8(x-4)+9-3(x+5)+38=0 | | 29x+5=30x+1 | | 8x-7+3-x=14-4x | | 99=-3x | | 8.3u+19.72-18.2u=-19.88-14.4u | | x*x+x-42=0 | | 8x-7+3-x=14+4x | | 6f+11.89=1.9f | | -4.41-11.9k=14.38-10.4k+8.96 | | 8x-7-3-x=14+4x | | -k(x-1)+2kx=1 | | 18.7-15.1b=-17.4b-19.02 | | x/.010 | | 8x+8=17x-3 | | -7.7p=-8.5p-11.2 | | -9r+17=-14-20-12r | | -8h+18=-10h | | X=ln21/ln8 | | 3k+m=10 | | 1+2c=4c+19 | | 5-3(4-2x)+3-2(5-x)=0 | | 4/5k=5/2 | | -8t=-13+20 |

Equations solver categories